Curiosity Unveiled: A Holistic Systematic Literature Review of Boarding School Students - Ghazali, Mas Yanti; Ahmad, Anuar; Mansor , Azlin Norhaini (Journal of Education Method and Learning Strategy, 2025)
This systematic literature review explores the diverse aspects of full-boarding school students worldwide. Despite its significance, there is a lack of a comprehensive synthesis of existing research on students in boarding schools. This review aims to bridge this gap by analyzing and structuring the available literature. The study employed the PRISMA approach and conducted systematic searches in academic databases such as Scopus and Web of Science to gather comprehensive studies, reviews, and articles related to students in boarding schools. The analysis was categorized into four themes that unveiled the objective of this study by utilizing advanced search techniques and keywords such as (1) "boarding schools," (2) "towards students," and (3) "for students.” The final finding data (n=26) were distilled into four primary themes through expert validation: (1) practices and learning strategies, (2) social-emotional well-being and mental health, (3) cultivation of spiritual values and character, and (4) barriers and challenges. The study has produced significant insights and suggestions, but additional research is needed to understand the long-term effects of these educational experiences on students' lives and future chances. Educational frameworks must be continuously assessed for efficacy and equality, particularly in the 21st century's ever-changing world.